Justice Reform or Facade Reform: The case of the Western Balkans - Halili Zenun (Sciendo, 2020)
EU transformative power is put into question and constantly challenged by the political actions of leaders in the Western Balkans. Although the political elites in this region have internalised a pro-European discourse, they are still guided and governed by authoritarian logic and practices colliding with the EU’s governing model. The paper analyses precisely this relationship between the EU and internal politics, namely, the transformative power/powerlessness of the EU towards the aspiring countries for membership in a single dimension; namely, justice. The paper reviews the reforms developed and the effects they have produced in the justice system in a calculation relation: costs and benefits. In this logic, this paper analyses costs and benefits of the internal elites of the Western Balkans, representing a classic oxymoron. On the one hand, pro-EU discourse is superficially used and, on the other, substantive actions are far from the EU’s governing model. The central argument emphasises that the reform process in the region has turned into a repetitive system of itself and destined to fail right from the beginning. So, we see a loss in reforms and plunging into a vicious circle, whereby each time elements increase and intensify but deteriorate one another, inevitably leading to the deterioration of the situation and producing multidimensional corruption.